APPLICATION OF SPECIFIC TYPE OF TRANSPORT ISSUE TO ANALYZE LOGISTICS PROBLEMS IN UKRAINE - Забуга, С. И.; Клименко, М. Н. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2016)
This article is devoted to one of the most important problems of the activity of any commercial enterprise, namely transport problems. Classical transport tasks have long been known and widely used as the solution of such problems. Nevertheless, the usage of the classical issues is practically limited in a particular situation, that may be connected with the activities of a particular enterprise, the political situation in the country, etc. Thus, the given article observes the basic problems of cargo transportation through the territory of Ukraine at the present stage. According to the main reasons, which have been identified and analyzed, the usage of the classical transportation issues is unacceptable to find the optimal transportation plan. Based on these reasons, the principles of formation of transport tasks of a specific type, namely transport issues with bans and transport issues with constraints, have been considered. It allows to use such methods to solve the problem of limited resources or lack of valid routes, depending on the selected task specification. For this purpose it was proposed to define a new transportation task, which also takes into account the restrictions on the supply and limited routes, which weren’t considered by the previous task. Thus, the main advantage of the new model is the efficiency of its use in the modern conditions on the territory of Ukraine. Taking into accont the conditions of solvability and optimality of transportation issues with bans and restrictions, for this task these conditions, as well as economically interpreted conditions, have been proposed. Numerical solutions for the real problems faced while minimizing transportation costs of «Barco» commercial enterprise, have been obtained.